The impact of cognitive reserve on neurocognitive performance in Major Depressive Disorder. (December 2018) - Venezia, Rachel G.; Gorlyn, Marianne; Burke, Ainsley K.; Oquendo, Maria A.; Mann, J. John; Keilp, John G.
Highlights: Cognitive reserve moderates neurocognitive deficits in MDD. Deficits in processing speed, memory, and executive functioning diminish with higher estimated intelligence. Deficits in interference processing diminish with increasing age. Abstract: Cognitive reserve may mitigate the degree of cognitive deficit observed in Major Depressive Disorder (MDD), confounding attempts to fully characterize the nature of these deficits. In this study, cognitive reserve was examined as a potential moderator of neurocognitive deficits in MDD. Unmedicated, currently depressed patients with MDD ( n  = 269), and healthy volunteers ( n  = 143) were compared on measures assessing psychomotor speed, interference processing, verbal memory, visual memory, and executive functioning. Moderating effects of education level and estimated intelligence level were examined as interactions, along with age, in a regression model for each test. Differences between patients and non-patients were found with most measures, and sustained in regression models as main effects. However, the interaction of estimated intelligence and patient status was significant for processing speed, verbal memory, visual memory, and executive functioning, with patient/non-patient differences diminishing with higher estimated intelligence. Neither estimated intelligence nor education level impacted interference processing differences, which were reduced with increasing age. Better intellectual ability moderates the effect of MDD on neurocognitive test performance. This effect may confound attempts to characterize these deficits in higher functioning samples. More challenging tasks may be needed, given the potential predictive value of neurocognition for differential therapeutic and clinical outcomes.